Webpack for beginners : your step-by-step guide to learning Webpack 4 - Bouzid, Mohamed (Apress, 2020)
Learn how to use Webpack from installation to configuration without the hassle of complex examples. Webpack has become one of the most popular module bundlers in recent years; its widely used by developers, companies, and organizations of all sizes, and many web frameworks use it for the management of their assets. If you are serious about web development these days then you must learn and understand Webpack. You will begin by installing and configuring Webpack, and learn how to write modular code. Youll then move onto understanding the usage of loaders and plugins with practical use cases, how to make aliases and resolve folders, cache busting, and installing third-party libraries such as jQuery, Bootstrap, QuillJS, and more. By the end of this book you will feel confident and ready to start using Webpack in your projects. Free from complex examples and intended to be as easy-to-follow as possible, this book is ideal for anyone who knows basic HTML, JavaScript, and how to work on the command line. Upgrade your developer skillset using Webpack for Beginners today. You will: Install and configure Webpack beyond the default settings Efficiently work with plugins and loaders Optimize Webpack for production Use instant refreshing with the Webpack dev server and hot module replacement Explore how to install some common JavaScript libraries.